The Association between Duration of Mechanical Ventilation, Age, and Microbial Patterns with the Incidence of Ventilator-Associated Pneumonia in the Intensive Care Unit of Gatot Soebroto Army Hospital - Vyona Rizky Mediosepti; Soroy Lardo; Maria Selvester Thadeus (PT. Berkah Digital Teknologi, 2025)
Abstract This study aims to investigate the relationship between duration of mechanical ventilator use, patient age, and bacterial patterns with the incidence of ventilator-associated pneumonia (VAP) in the ICU room at RSPAD Gatot Soebroto. This study used an analytical observational approach involving 97 patients as respondent who were using mechanical ventilators in the ICU. Data analysis shows that there is a significant relationship between the length of use of a mechanical ventilator and the incidence of VAP. The longer the patient uses a mechanical ventilator, the higher the risk of VAP. In addition, patient age also has a significant relationship with the incidence of VAP, where older patients have a higher risk of VAP. The pattern of bacteria detected also influences the incidence of VAP, with the type of bacteria involved in the infection influencing the risk of VAP. Based on these findings, several suggestions can be proposed to improve the management and prevention of VAP. Among them are the implementation of strict hygiene protocols, increasing education and training of medical personnel, more intensive patient monitoring and supervision, proper identification and management of bacterial infections, and the need for further research with better designs. In conclusion, this study contributes to the understanding of factors associated with the incidence of VAP and may serve as a basis for better prevention and management efforts in reducing the incidence of VAP in the intensive care setting. However, further research is needed to validate these findings and develop more effective prevention strategies. Abstrak Purpose: Menyelidiki hubungan antara Lama Penggunaan Ventilator Mekanik, Usia pasien, dan Pola Bakteri dengan Kejadian Ventilator Associated Pneumonia (VAP) di Ruang ICU RSPAD Gatot Soebroto. Research Methodology: Penelitian ini menggunakan pendekatan observasional analitik dengan melibatkan 97 pasien sebagai responden. Data dikumpulkan dari pasien yang menggunakan ventilator mekanik di ruang ICU, dan analisis data dilakukan untuk mengevaluasi hubungan antara variabel yang diteliti. Results: Analisis menunjukkan adanya hubungan signifikan antara Lama Penggunaan Ventilator Mekanik dan Kejadian VAP. Semakin lama pasien menggunakan ventilator mekanik, semakin tinggi risiko terjadinya VAP. Usia pasien yang lebih tua juga berhubungan signifikan dengan kejadian VAP, dan pola bakteri yang terdeteksi mempengaruhi risiko terjadinya infeksi. Limitations: Penelitian ini tidak mempertimbangkan faktor konfounding yang mungkin mempengaruhi hasil, serta keterbatasan dalam generalisasi temuan karena lokasi penelitian yang spesifik. Contribution: Penelitian ini memberikan kontribusi pada pemahaman faktor-faktor yang berhubungan dengan Kejadian VAP dan dapat menjadi dasar untuk upaya pencegahan dan manajemen VAP di lingkungan perawatan intensif, serta berguna dalam bidang kedokteran dan keperawatan.